Singapore Undiagnosed Disease Program: Genomic Analysis aids Diagnosis and Clinical Management. Issue 1 (20th August 2020) - Bhatia, Neha S; Lim, Jiin Ying; Bonnard, Carine; Kuan, Jyn-Ling; Brett, Maggie; Wei, Heming; Cham, Breana; Chin, Huilin; Bosso-Lefevre, Celia; Dharuman, Perumal; Escande-Beillard, Nathalie; Devasia, Arun George; et al.
Abstract : Objective: Use next-generation sequencing (NGS) technology to improve our diagnostic yield in patients with suspected genetic disorders in the Asian setting. Design: A diagnostic study conducted between 2014 and 2019 (and ongoing) under the Singapore Undiagnosed Disease Program. Date of last analysis was 1 July 2019. Setting: Inpatient and outpatient genetics service at two large academic centres in Singapore. Patients: Inclusion criteria: patients suspected of genetic disorders, based on abnormal antenatal ultrasound, multiple congenital anomalies and developmental delay. Exclusion criteria: patients with known genetic disorders, either after clinical assessment or investigations (such as karyotype or chromosomal microarray). Interventions: Use of NGS technology—whole exome sequencing (WES) or whole genome sequencing (WGS). Main outcome measures: (1) Diagnostic yield by sequencing type, (2) diagnostic yield by phenotypical categories, (3) reduction in time to diagnosis and (4) change in clinical outcomes and management. Results: We demonstrate a 37.8% diagnostic yield for WES (n=172) and a 33.3% yield for WGS (n=24). The yield was higher when sequencing was conducted on trios (40.2%), as well as for certain phenotypes (neuromuscular, 54%, and skeletal dysplasia, 50%). In addition to aiding genetic counselling in 100% of the families, a positive result led to a change in treatment in 27% of patients. Conclusion: Genomic sequencing is an effective method for diagnosing rare disease or previous 'undiagnosed' disease. The clinical utility of WES/WGS is seen in the shortened time to diagnosis and the discovery of novel variants. Additionally, reaching a diagnosis significantly impacts families and leads to alteration in management of these patients.